2006
DOI: 10.1016/j.cub.2006.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase-1 Controls Proteasome-Dependent Degradation of Claspin during Checkpoint Recovery

Abstract: DNA-damage checkpoints maintain genomic integrity by mediating a cell-cycle delay in response to genotoxic stress or stalled replication forks. In response to damage, the checkpoint kinase ATR phosphorylates and activates its effector kinase Chk1 in a process that critically depends on Claspin . However, it is not known how exactly this kinase cascade is silenced. Here we demonstrate that the abundance of Claspin is regulated through proteasomal degradation. In response to DNA damage, Claspin is transiently st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
224
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(237 citation statements)
references
References 13 publications
9
224
0
2
Order By: Relevance
“…Three papers published during the review of this manuscript have identified amino acids 29-34 of Claspin as a phosphorylation-dependent proteasomal degradation motif required for binding of the ubiquitin ligase SCF b-TrCP to Claspin. [22][23][24] However, mutation of Ser30 and Ser34, which has been shown to abolish SCF b-TrCP -mediated degradation of Claspin [22][23][24] did not increase the stability of a caspaseresistant Claspin construct in apoptotic cells. These data indicate that the stability of Claspin during apoptosis is regulated by a ubiquitin ligase and/or a degradation signal different from that responsible for its degradation during normal cell cycle progression and recovery from checkpoint arrest.…”
Section: Discussionmentioning
confidence: 94%
“…Three papers published during the review of this manuscript have identified amino acids 29-34 of Claspin as a phosphorylation-dependent proteasomal degradation motif required for binding of the ubiquitin ligase SCF b-TrCP to Claspin. [22][23][24] However, mutation of Ser30 and Ser34, which has been shown to abolish SCF b-TrCP -mediated degradation of Claspin [22][23][24] did not increase the stability of a caspaseresistant Claspin construct in apoptotic cells. These data indicate that the stability of Claspin during apoptosis is regulated by a ubiquitin ligase and/or a degradation signal different from that responsible for its degradation during normal cell cycle progression and recovery from checkpoint arrest.…”
Section: Discussionmentioning
confidence: 94%
“…Under these conditions, Chk1 activity also remains high and hence the checkpoint remains engaged [34]. Several independent studies identified that this accumulation of Claspin is due to a defect in its' ubiquitin-dependent proteolysis by SCF complexes containing the β-TrCP F-box protein [35][36][37].…”
Section: Ubiquitin-dependent Proteolysis Of Activated Checkpoint Protmentioning
confidence: 99%
“…Dysfunction of topoIIa might generate DNA strand breaks and activate the DNA-damage checkpoint. In contrast, Plk1 is a target of the DNA-damage checkpoint and is required for checkpoint recovery after the damage has been completely repaired (Smits et al, 2000;Mamely et al, 2006). Plk1 interacts with several checkpoint components, such as p53 and Chk2 (Tsvetkov et al, 2003;Ando et al, 2004).…”
Section: Plk1 Depletion Activates Checkpointmentioning
confidence: 99%